2019
DOI: 10.1093/cvr/cvz164
|View full text |Cite
|
Sign up to set email alerts
|

Chanzyme TRPM7 protects against cardiovascular inflammation and fibrosis

Abstract: Aims Transient Receptor Potential Melastatin 7 (TRPM7) cation channel is a chanzyme (channel + kinase) that influences cellular Mg2+ homeostasis and vascular signalling. However, the pathophysiological significance of TRPM7 in the cardiovascular system is unclear. The aim of this study was to investigate the role of this chanzyme in the cardiovascular system focusing on inflammation and fibrosis. Methods and results TRPM7-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 51 publications
1
106
0
Order By: Relevance
“…These results indicate that TRPM7 deletion in myocytes during the developmental stage (E9.5 to E12.5) can cause impaired adult heart function, whereas deletion of TRPM7 after embryonic day 13 does not produce any effects on normal heart function [190]. Interestingly, a recent study by Rios and colleagues reported that TRPM7-deficient mice with kinase domain deletion (TRPM7 +/∆kinase ) exhibit cardiac hypertrophy, fibrosis, and inflammation [219]. It was suggested that TRPM7 plays both anti-fibrotic and anti-inflammatory roles [219].…”
Section: Trpm Channels and Cardiac Fibrosismentioning
confidence: 93%
See 1 more Smart Citation
“…These results indicate that TRPM7 deletion in myocytes during the developmental stage (E9.5 to E12.5) can cause impaired adult heart function, whereas deletion of TRPM7 after embryonic day 13 does not produce any effects on normal heart function [190]. Interestingly, a recent study by Rios and colleagues reported that TRPM7-deficient mice with kinase domain deletion (TRPM7 +/∆kinase ) exhibit cardiac hypertrophy, fibrosis, and inflammation [219]. It was suggested that TRPM7 plays both anti-fibrotic and anti-inflammatory roles [219].…”
Section: Trpm Channels and Cardiac Fibrosismentioning
confidence: 93%
“…Interestingly, a recent study by Rios and colleagues reported that TRPM7-deficient mice with kinase domain deletion (TRPM7 +/∆kinase ) exhibit cardiac hypertrophy, fibrosis, and inflammation [219]. It was suggested that TRPM7 plays both anti-fibrotic and anti-inflammatory roles [219]. However, since TRPM7 channel activity was impaired in the TRPM7 +/∆kinase mice [220], it is plausible that the disrupted TRPM7 channel function during the developmental stage (E9.5 to E12.5) may have contributed to the impaired heart function, resulting in the observed cardiac hypertrophy, inflammation, and fibrosis in the TRPM7 +/∆kinase mice [219].…”
Section: Trpm Channels and Cardiac Fibrosismentioning
confidence: 99%
“…Importantly, treatment with anti-TGF-β antibody ameliorates progressive kidney damage via inhibition of TGF-β/Smad signaling pathway 27 . In hepatic and cardiac fibrosis, TRPM7 is upregulated by TGF-β1 stimulation and Smad2/3 phosphorylation 10,36 . In addition, a recent report showed that Smad2 is a substrate of the TRPM7 kinase 3,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Trpm7 in mice disrupts cardiac automaticity and causes cardiac hypertrophy and fibrosis. 40,54 In ischemic cardiomyopathy, TRPM7 was significantly down regulated in the left atria and ventricle. 39 However, in non-ischemic dilated cardiomyopathy, TRPM7 was shown to be upregulated in patients with ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%